Occurrence and recurrence of diabetes in pregnancy. Issue 4 (17th March 2013) - Khambalia, A. Z.; Ford, J. B.; Nassar, N.; Shand, A. W.; McElduff, A.; Roberts, C. L.
Abstract Aims To determine occurrence and recurrence rates of gestational diabetes among women having at least two consecutive pregnancies. Risk factors for recurrence of gestational diabetes and rates of second/third pregnancy pre‐existing diabetes mellitus were also assessed. Methods Population‐based study using longitudinally linked hospital discharge and birth records (2001–2009) in NSW, Australia. Participants included women without a pre‐existing diagnosis of Type 1 or Type 2 diabetes at time of first pregnancy and with at least a first and second birth. Factors associated with recurrence of gestational diabetes were examined using multivariate log‐binomial models to adjust for correlation within mothers and estimate relative risks and 95% confidence intervals. Results First occurrence of gestational diabetes was 3.7% (5315/142 843) in the first pregnancy and 2.7% (3689/137 528) in the second pregnancy. The recurrence rate of gestational diabetes in a second consecutive pregnancy was 41.2%. Risk of pre‐existing diabetes in a pregnancy subsequent to one with first occurrence of gestational diabetes was 2.2% and 2.0% in the second or third pregnancy, respectively. Among women with a diagnosis of gestational diabetes in the first pregnancy, independent predictors of gestational diabetes recurrence were maternal age ≥ 35 years, ethnicity (Middle East/North Africa and Asia), pregnancy hypertension, large for gestational age infant and preterm birth in the first pregnancy, longer inter‐pregnancy birth interval and pregnancy hypertension and multiple pregnancy in the second pregnancy. Conclusions Gestational diabetes in a previous pregnancy is a strong indicator of future risk and a useful clinical marker for identifying women at elevated risk in a subsequent pregnancy.